2019
DOI: 10.1016/j.adhoc.2018.10.001
|View full text |Cite
|
Sign up to set email alerts
|

On the performance of non-orthogonal multiple access in the finite blocklength regime

Abstract: In this paper, we present a finite-block-length comparison between the orthogonal multiple access (OMA) scheme and the non-orthogonal multiple access (NOMA) for the uplink channel. First, we consider the Gaussian channel, and derive the closed form expressions for the rate and outage probability. Then, we extend our results to the quasi-static Rayleigh fading channel. Our analysis is based on the recent results on the characterization of the maximum coding rate at finite block-length and finite block-error pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…where Pr (γ D1 < x) in (31) is given by (16). From (31), an approximate closed-form expression for the ergodic capacity of D 1 can be obtained, as presented in the following proposition.…”
Section: A Ergodic Capacity At Dmentioning
confidence: 99%
See 1 more Smart Citation
“…where Pr (γ D1 < x) in (31) is given by (16). From (31), an approximate closed-form expression for the ergodic capacity of D 1 can be obtained, as presented in the following proposition.…”
Section: A Ergodic Capacity At Dmentioning
confidence: 99%
“…A large number of destinations multiplexed in the power domain might not be feasible in practice, since the processing complexity of SIC at receivers grows non-linearly with the number of users. This complexity is more evident when SIC error propagation is assumed; therefore, two power-domain NOMA users is a practical assumption[28][29][30][31].…”
mentioning
confidence: 99%
“…In particular, closed-form expressions for the block error rates of a two-users NOMA network have been derived, while demonstrating the superior performance of NOMA over OMA in reducing transmission latency. Closed-form expressions for the rate and outage probability in an UL NOMA scenario with two users have been derived in [27] for the Gaussian and Rayleigh fading channels. Furthermore, the authors investigated the trade-off between reliability and throughput in the ARQ regime, and demonstrated that NOMA is always superior to OMA in terms of throughput, reliability, and latency.…”
Section: ) Gb-noma Accessmentioning
confidence: 99%
“…Kotaba et al introduced the concept of NOMA-HARQ to solve bandwidth limitations during retransmission [18]. Dosti et al presented an FBL comparison between the OMA and NOMA schemes for an uplink channel in a Gaussian channel and a Rayleigh fading channel [19].…”
Section: Introductionmentioning
confidence: 99%